2022
DOI: 10.1111/gcbb.12993
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect interactions between biochar properties, plant belowground traits, and plant performance

Abstract: Biochar is more and more widely recognized as a promising agricultural amendment improving yield and ecosystem services in a range of different contexts. However, underlying mechanisms contributing to biochars benefits, notably biochar–root interactions, and their mediation by biochar's diverse properties remain unclear and poorly quantified. This study aimed to examine and quantify the interactions between biochar properties and plant traits and their effect on plant performance. To gain a better understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…These authors concluded that the availability of calcium and magnesium nutrients in biochar is greatly influenced by both the feedstock and particle size. In another study, the release of carboxylates from barley roots was increased by up to 300% by the application of biochar amended with phosphorus (Honvault et al, 2022). Carboxylates, organic acids that help solubilize nutrients in the soil, can play a crucial role in the solubilization of nutrients in the soil.…”
Section: Nutrient Availabilitymentioning
confidence: 99%
“…These authors concluded that the availability of calcium and magnesium nutrients in biochar is greatly influenced by both the feedstock and particle size. In another study, the release of carboxylates from barley roots was increased by up to 300% by the application of biochar amended with phosphorus (Honvault et al, 2022). Carboxylates, organic acids that help solubilize nutrients in the soil, can play a crucial role in the solubilization of nutrients in the soil.…”
Section: Nutrient Availabilitymentioning
confidence: 99%